KEANEKARAGAMAN JENIS-JENIS MOLLUSCA (Bivalvia DAN Gastropoda) DIPANTAI OESOSOLE SEBAGAI SUMBER BELAJAR BIOLOGI DALAM BENTUK BOOKLET - Sonya Titin M Nge; Novi Ivonne Bullu; Novika M Lusi (Postgraduate, University of Mataram, 2023)
Mollusca has two largest class members, namely Bivalvia and Gastropoda. Gastropods are characterized by a single-threaded shell. Meanwhile, Bivalves have two shells that are connected dorsally. This research aims to determine the types of mollusks (Bivalvia and Gastropods), the diversity index, and the use of research results in booklet form. This research was conducted at Oesosole Beach, East Rote District, Rote Ndao Regency, East Nusa Tenggara Province in April 2023. The research method used was quadratic transects with R and D. The results of the research showed that the types of Bivalves and Gastropods found were the Bivalvia class, consists of 8 families with 10 species. Meanwhile, gastropods consist of 7 families with 9 species. The diversity index value for Bivalves and gastropods is classified as moderate. Bivalves with a value of H'= 1.57 and gastropods with a value of H'= 1.08. Utilization of research results as a learning resource in the form of booklets obtained results from validator tests and user trials with a score of 90.75%. This shows that the bivalve and gastropod booklets are of very good qualifications. The bivalves found on Oesosole Beach consisted of 10 species and 9 species of gastropods. The diversity index for Bivalves and gastropods is in the medium category. Utilization of research results in booklet form is suitable for use in the learning process. Â